1960
DOI: 10.1002/hlca.19600430151
|View full text |Cite
|
Sign up to set email alerts
|

Etudes sur les matières végétales volatiles CLXVI. Présence de β‐déhydro‐elsholtzione dans l'huile essentielle d'Elsholtzia oldhami HEMSL

Abstract: Beside elsholtzione, the essential oil of Elsholtzia oldhami HEMSL. contains dehydro‐elsholtzione, which is a 3‐methyl‐2‐(3‐methyl‐1‐oxo‐2‐butenyl)‐furan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

1960
1960
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 9 publications
0
10
1
Order By: Relevance
“…2-Isovaleryl-3-methylfuran (16) is also reported to be present in the essential oils of other Elsholtzia species like E. oldhami (3,8), E. ciliata (11)(12)(13), and the E. cristata (3,4) which differs in its oil composition from the one investigated here.…”
Section: Resultscontrasting
confidence: 47%
See 2 more Smart Citations
“…2-Isovaleryl-3-methylfuran (16) is also reported to be present in the essential oils of other Elsholtzia species like E. oldhami (3,8), E. ciliata (11)(12)(13), and the E. cristata (3,4) which differs in its oil composition from the one investigated here.…”
Section: Resultscontrasting
confidence: 47%
“…The JR spectrum of the essential oil contained characteristic absorption bands at 3125 (C-H), 1580 and 1512 (heterocyclic), and at 885 cm1, known for furan derivatives (7), and at 1657 (C = 0) and 1616 (C = C), consistent with the spectrum of synthetic dehydroelsholtzia ketone (8). Furthermore, the 2,4-dinitrophenyl hydrazone of the major component was prepared (m.p.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The constituents of the essential oils from various Elsholtzia species have been analysed and among others, terpenoids, unsaturated alcohols, carboxylic acids and esters have been identified. Acylfuran derivatives like elsholtziaketone ['= 2isovaleryl-3-methylfuran], a-dehydroelsholtziaketone [= 3methyl-2-(3-methylbut-3-enoyl)-furan] and f3-dehydroelsholtziaketone [= naginataketone, 3-methyl-2-(3-methylbut-2enoyl)-furan] are the characteristic compounds in E. ciliata (10), E. densa (11), E. oldhami (12) and E. patrini (13). Except our preliminary report (14) nothing has been reported on the chemical composition of the essential oil from E. strobilifera.…”
Section: Introductionmentioning
confidence: 99%
“…1 The structure was elucidated in 1961 by Seidel et al 2 Since that time rose oxide has been detected in many plants (e.g., Pelargonium spp., 3 Ribes nigrum L., 4 Cymbopogon winterianus Jowitt 5 ) and even in the liquid secretion of the wide-spread beetle Aromia moschata L. 6 Recently, it was shown that (−)-cisrose oxide 2 has a much lower odor threshold value than (+)-cis-1 and the trans-isomers 3,4. 2 contributes substantially to the unique bloomy green top notes of geranium and rose oils.…”
Section: Rose Oxide (Cis-and Trans-4-methyl-2-(2-methyl-1-mentioning
confidence: 99%